2016
DOI: 10.5888/pcd13.160056
|View full text |Cite|
|
Sign up to set email alerts
|

The High Prevalence of Diabetes in a Large Cohort of Patients Drawn From Safety Net Clinics

Abstract: IntroductionUnderserved populations have been overlooked or underrepresented in research based on data from diabetes registries. We estimated diabetes prevalence using a cohort developed from the electronic health records of 3 networks of safety net clinics that provide care to underserved populations.MethodsADVANCE (Accelerating Data Value Across a National Community Health Center Network) is a partnership of the OCHIN Community Health Information Network (OCHIN), the Health Choice Network (HCN), and the Fenw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The patients served in community clinical settings or health systems experience a broad range of healthcare environments, social determinants of health, and complex co-morbidities [ 51 ]. The results of research studies in these settings would be more representative of those communities than results of research carried out in academic settings, which tend to be highly selective with respect to patients, providers and healthcare environments [ 49 52 ].…”
Section: Discussion- Recommendationsmentioning
confidence: 99%
“…The patients served in community clinical settings or health systems experience a broad range of healthcare environments, social determinants of health, and complex co-morbidities [ 51 ]. The results of research studies in these settings would be more representative of those communities than results of research carried out in academic settings, which tend to be highly selective with respect to patients, providers and healthcare environments [ 49 52 ].…”
Section: Discussion- Recommendationsmentioning
confidence: 99%
“…To date, there are limited studies evaluating the feasibility and efficacy of this team care approach, 9 especially in safety-net clinics that serve a greater number of patients who are uninsured. 10 According to the 2020 Standards of Medical Care in Diabetes, the use of multidisciplinary teams including primary care physicians, nurses, dietitians, pharmacists, and mental health professionals ranks only as an expert consensus because of limited clinical data. 11 Preliminary studies have shown that treatment of diabetes in multidisciplinary teams with pharmacists or behavioral health professionals is associated with decreased A1c concentrations [12][13][14][15] and more rapid attainment of associated goals.…”
Section: Introductionmentioning
confidence: 99%
“…Patient coauthors have advised, guided, and been published on accepted manuscripts, including key reviews and contributions from PEP member coauthors with lived experience of the condition of study. 32 Patient investigators have presented at national and international conferences and coauthored research proposals and manuscripts. 33 , 34 ADVANCE patient and clinician leaders recently acted as copresenters in the 2016 OCHIN Learning Forum (a national conference), with 5 PEP members and 2 PBRN steering committee members supporting 5 panels covering the impacts of the Affordable Care Act, stakeholder engagement, patient portal adoption, and enhancement and the OpenNotes movement, which provides patient access to visit notes through their patient portal.…”
Section: Phase II Engagementmentioning
confidence: 99%